isnt the same as
P ( E ) + P ( F ) = - P ( E ∩ F ) + P ( E ∪ F ) ?
Hi guys, again please check my work(bold is my answer). But the last one i don't know.
consider events E and F in a sample space S
P ( E ) + P ( F ) ≥ 0 for any events E and F . (a) True (b) False
P ( E ) + P ( F ) ≤ 100 % for any events E and F . (a) True (b) False
P ( E ) ⋅ P ( F ) ≤ 100 % for any events E and F . (a) True (b) False
For any eventsE and F , P ( E ) − P ( F ) = P ( E ∩ F ) − P ( E ∪ F ) .
(a) True (b) False
For any eventsE and F , − P ( E ) − P ( F ) = P ( E ∩ F ) − P ( E ∪ F ) .
(a) True (b) False